Risk and return characteristics of environmentally and socially responsible firms in Spain during a financial downturn: 2008–2011 - P. Ruiz-Palomino; R. del Pozo-Rubio; R. Martínez-Ca\~nas (South African Journal of Business Management, 2015)
The onset of the global financial crisis in 2008 undermined trust in financial markets, with immediate damages to businesses and enduring negative effects for numerous national economies. The situation also has endangered progress in terms of investments in environmental and social management (ESM) Issues, because managers may be more likely to embrace the misguided notion that such investments represent a non-returnable costs that will hinder firms' financial performance. Yet ESM is needed now more than ever, because "doing good and doing well" messages are highly appreciated by stakeholders and can substantially improve a firm's competitiveness. This article analyzes the performance of the Spanish FTSE4Good IBEX index, compared with that of the Spanish IBEX 35 index, during the financial crisis and reveals slightly better performance for the former. Thus, considering the difficult financial context, indicators of good environmental and social performance, among other factors, might have positive effects on stock index performance. The findings offer some key implications for managerial practice.
Keywords: 650